Community pharmacists’ perceived value on precision medicine, desired training components, and exposure during pharmacy education: Malaysia’s experience - Naimat, Faiza; Fahrni, Mathumalar Loganathan; Purushothaman, Shankar; Abdul Ghani, Mohamad Nizam; Chumnumwat, Supatat; Babar, Zaheer-Ud-Din (Frontiers in Pharmacology, 2022)
Background: Precision medicine beckons new horizons for therapy geared to one’s genetics, lifestyle, and environmental determinants. Molecular, pathology, and clinical diagnostics can be integrated to provide pharmaceutical care. Aims: The value and appeal of precision medicine to community pharmacists, knowledge attained, and training programmes perceived as necessary were evaluated. Methods: Over 10 months, a published questionnaire, which was also digitally accessible during the COVID-19 outbreak, was distributed by hand, via email and social media. 300 community pharmacists across 9 districts in an urban state in Malaysia, self-administered and returned completed versions (response rate 75%). Three- or five-point Likert scale and multiple-choice responses were analysed using SPSS to assess whether or not exposure through the pharmacy curricula impacted current knowledge, perception and willingness to pursue precision medicine. Results: Respondents were largely: females (N = 196, 65.3%) and practicing for up to 10 years (N = 190, 66.3%). Although knowledge levels were moderate (76%), positive perceptions were showcased (94%), and 80% were willing to integrate precision medicine into their daily practice. Although 61% did not or do not recall having had prior exposure to pharmacogenomics as part of their pharmacy school curricula, many (93%) were willing to attain knowledge by undergoing additional training. Desired training included current pharmacogenetic testing available (17%), interpretation of the test results (15%), and ethical considerations (13%). Community pharmacists who had 0.5–10 years’ work experience possessed greater knowledge (μ = 1.48, CI 1.35–1.61, p = 0.017), than the pharmacists who had 21–40 years of work experience (μ = 1.28, CI 1.05–1.51, p = 0.021). Exposure to the subject during pharmacy education positively impacted the willingness to integrate precision medicine in daily practice (p = 0.035). Conclusion: Community pharmacists were receptive to and valued precision medicine. A relatively high number had prior exposure to concepts of precision medicine through the pharmacy curriculum, and were therefore willing to adopt the practice in their day-to-day provision of healthcare. With adequate training centred on bioethics, utilising pharmacogenetic testing, and interpretation of the results, community pharmacists will be equipped for the provision of precision medicine services in the foreseeable future.